Mesoproterozoic continental arc magmatism and crustal growth in the eastern Central Tianshan Arc Terrane of the southern Central Asian Orogenic Belt: Geochronological and geochemical evidence - He, Zhenyu; Klemd, Reiner; Zhang, Zeming; Zong, Keqing; Sun, Li-Xin; Tian, Zuolin; Huang, Bo-Tao (Lithos, 2015)
Numerous microcontinents are known to occur in the Central Asian Orogenic Belt (CAOB), one of the largest accretionary orogens and the most significant area of Paleozoic crustal growth in the world. The evolution of the Precambrian crust in these microcontinents is central to understanding the accretionary and collisional tectonics of the CAOB. Here, we present systematic zircon U–Pb dating and Hf isotope studies of Mesoproterozoic gneissic granitoids from the eastern Central Tianshan Arc Terrane (CTA) of the southern CAOB. The investigated intermediate to felsic (SiO2 = 60.48–78.92 wt.%) granitoids belong to the calcic- to calc-alkaline series and usually have pronounced negative Nb, Ta and Ti anomalies, relative enrichments of light rare earth elements (LREEs) and large ion lithophile elements (LILEs) while heavy rare earth elements (HREEs) and high field strength elements (HFSEs) are depleted, revealing typical active continental margin magmatic arc geochemical characteristics. These spatially-distant rocks show consistent zircon U–Pb crystallization ages from ca. 1.45 to 1.40 Ga and thus constitute a previously unknown Mesoproterozoic continental magmatic arc covering hundreds of kilometers in the eastern segment of the CTA. Furthermore the high and mainly positive zircon εHf(t) values between − 1.0 and + 8.6 and the zircon Hf model ages of 1.95 to 1.55 Ga, which are slightly older than their crystallization ages, suggest that they were mainly derived from rapid reworking of juvenile material with a limited input of an ancient crustal component. Therefore, the formation of these granitoids defines an extensive Mesoproterozoic intermediate to felsic, subduction-related intrusive magmatic arc activity that was active from at least 1.45 to 1.40 Ga, involving significant juvenile continental growth in the eastern segment of the CTA. Furthermore the zircon U–Pb and Hf isotopic data challenge the common belief that the CTA was part of the Tarim Craton during Paleo- to Mesoproterozoic times. However, the southern Beishan microcontinents and the CTA have similar zircon U–Pb and Hf isotopic signatures, indicating a similar Precambrian tectonothermal evolution for both. This finding provides new and important constraints on the Precambrian crustal evolution of the microcontinents in the southern CAOB.<br
Keywords: Zircon U–Pb geochronology and Hf isotopes; Crustal growth; Mesoproterozoic continental magmatic arc; Chinese Eastern Tianshan; Central Asian Orogenic Belt